Robust electrocatalysts from an alloyed Pt–Ru–M (M = Cr, Fe, Co, Ni, Mo)-decorated Ti mesh for hydrogen evolution by seawater splitting. Issue 17 (14th April 2016) - Li, Hongyan; Tang, Qunwei; He, Benlin; Yang, Peizhi
Abstract : A prerequisite for creating green hydrogen energy is to develop cost-effective electrocatalysts with reduced overpotentials, increased current density, and therefore enhanced catalytic activity toward water splitting. Abstract : A prerequisite for creating green hydrogen energy is to develop cost-effective electrocatalysts with reduced overpotentials, increased current density, and therefore enhanced catalytic activity toward water splitting. We present here the fabrication of an alloyed Pt–Ru–M (M = Cr, Fe, Co, Ni, Mo)-decorated titanium mesh by a simple electrodeposition technique. The resultant electrocatalysts were thoroughly characterized and evaluated by catalyzing seawater splitting. The preliminary results demonstrate that the titanium-mesh-supported Pt–Ru–M electrodes have markedly enhanced catalytic activity for the hydrogen evolution reaction in comparison to the corresponding Pt or Pt–Ru electrode, arising from the alloying effects between the transition metals and Pt species. Moreover, the resultant Pt–Ru–Mo alloy electrodes show remarkable stability over 172 h of operation, suggesting their promise for use in practical applications.